Co-Amorphous Versus Deep Eutectic Solvents Formulations for Transdermal Administration - Yannick Guinet; Laurent Paccou; Alain Hédoux (MDPI AG, 2023)
Transdermal administration can be considered as an interesting route to overcome the side-effects inherent to oral intake. Designing topical formulations with maximum drug efficiency requires the optimization of the permeation and the stability of the drug. The present study focuses on the physical stability of amorphous drugs within the formulation. Ibuprofen is commonly used in topical formulations and then was selected as a model drug. Additionally, its low Tg allows easy, unexpected recrystallization at room temperature with negative consequence on skin penetration. In this study, the physical stability of amorphous ibuprofen was investigated in two types of formulations: (i) in terpenes-based deep eutectic solvents (DES) and (ii) in arginine-based co-amorphous blends. The phase diagram of ibuprofen:L-menthol was mainly analyzed by low-frequency Raman spectroscopy, leading to the evidence of ibuprofen recrystallization in a wide range of ibuprofen concentration. By contrast, it was shown that amorphous ibuprofen is stabilized when dissolved in thymol:menthol DES. Forming co-amorphous arginine-ibuprofen blends by melting is another route for stabilizing amorphous ibuprofen, while recrystallization was detected in the same co-amorphous mixtures obtained by cryo-milling. The mechanism of stabilization is discussed from determining Tg and analyzing H-bonding interactions by Raman investigations in the C=O and O-H stretching regions. It was found that recrystallization of ibuprofen was inhibited by the inability to form dimers inherent to the preferential formation of heteromolecular H-bonding, regardless of the glass transition temperatures of the various mixtures. This result should be important for predicting ibuprofen stability within other types of topical formulations.